Ontology-based provisioning for technology-independent multi-layer transport networks - Barcelos, Pedro Paulo Favato (2015)
Provisioning is an important activity in the configuration of networks. The ITU-T Recommendation M.3400 defines network provisioning as the "procedures which are necessary to bring an equipment into service, not including installation". Resource and service provisioning are recent challenges in communication network planning and important activities in paradigms of future networking, like service-oriented networks, cloud networking, and network virtualization. Considering the problems identified in the literature, this thesis investigates the use of semantic technologies, especially ontologies, to solve the lack of interoperability in the transport network area and the use of these technologies as the basis for a computational solution that can provision technology-independent multi-layer transport networks considering the networks equipment states. This thesis contributes to the network provisioning area, a subarea of network management, by developing an ontology-based provisioning solution for technology-independent multi-layer transport networks. To accomplish this objective, (i) an Ontology Reference Model for technology-independent multilayer transport networks based on the Recommendation ITU-T G.800 was built with an expressive well-founded ontology language to the definition of precise semantics. The Ontology Reference Model allows communication, learning, and interoperation in the transport network area. In addition, (ii) a semantically improved network model for the provisioning of transport networks, here called OWL Computational Ontology, was generated from the Ontology Reference Model through a rigid ontology engineering; and (iii) an ontology-based network provisioning knowledge-based system that uses the OWL Computational Ontology as a knowledge base was implemented. Results of a test on an Optical Transport Network example confirm that the developed system is able to perform circuit provisioning and connection provisioning on multi-layer transport networks considering the equipment states.